The Disposition of Motivational Strategies among English Language Teachers in Public Universities in Malaysia - Omar, Suhaida; Azim, Nik Ahmad Farhan Nik (Journal of ELT Research, 2019)
The English language is one of the compulsory subjects in both primary and secondary schools in Malaysia. In the case of motivation in teaching and/or learning English, there has been an increase on the research on motivation in language teaching, i.e. teachers’ motivation but little attention is given to language teachers’ motivation in higher education institutions (HIEs). This was a pilot case study to gain a better understanding of the HIEs language teachers‘perceptions on the importance and the frequency of usage of the motivational strategies. The method used for data collection was online questionnaire from 17 English language teachers from 4 public universities in Malaysia.  The findings from this pilot study were analysed using descriptive and inferential statistics and they revealed that they perceived the motivational strategies as important and implemented those strategies in their English classes. Besides that, those who perceived high importance of motivational strategies reported high frequency of implementing strategies as well. It is hoped that this pilot study managed to fulfil the knowledge gap on the lack of information about language teachers’ motivation in HIEs and could be used to promote further research in this area in a larger range of HIEs across Malaysia.